2019
DOI: 10.1111/age.12866
|View full text |Cite
|
Sign up to set email alerts
|

A candidate‐SNP retrospective cohort study for fracture risk in Japanese Thoroughbred racehorses

Abstract: SummaryFractures are medical conditions that compromise the athletic potential of horses and/or the safety of jockeys. Therefore, the reduction of fracture risk is an important horse and human welfare issue. The present study used molecular genetic approaches to determine the effect of genetic risk for fracture at four candidate SNPs spanning the myostatin (MSTN) gene on horse chromosome 18. Among the 3706 Japanese Thoroughbred racehorses, 1089 (29.4%) had experienced fractures in their athletic life, indicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 23 publications
1
11
0
Order By: Relevance
“…These effects could reflect multiple factors, including biology, wear and tear, and pathophysiology, as well as genetic contributions [45]. Recent evidence suggests a sex-differentiated genetic predisposition to fracture that also relates to superior performance ability [46], implying selection for speed may simultaneously select for fracture predisposition, as may speed itself [15]. Imperatives that drive selection and work stresses reflect industry practices and expectations, and these same forces also influence how age and sex are associated with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…These effects could reflect multiple factors, including biology, wear and tear, and pathophysiology, as well as genetic contributions [45]. Recent evidence suggests a sex-differentiated genetic predisposition to fracture that also relates to superior performance ability [46], implying selection for speed may simultaneously select for fracture predisposition, as may speed itself [15]. Imperatives that drive selection and work stresses reflect industry practices and expectations, and these same forces also influence how age and sex are associated with mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic associations with stress fractures have been identified in elite human athletes 82 and the potential for genomic screening has been suggested for Thoroughbred racehorses 83–85 . However, a recent systematic review found few associations 86 .…”
Section: Potential Screening Toolsmentioning
confidence: 99%
“…Genetic associations with stress fractures have been identified in elite human athletes 82 and the potential for genomic screening has been suggested for Thoroughbred racehorses. [83][84][85] However, a recent systematic review found few associations. 86 The heritability of musculoskeletal injury has been reported from various populations 84,87,88 and evidence that certain genotypes may predispose individual horses to fracture has been obtained from molecular studies, 89 prompting some to speculate that targeted breeding strategies and/or genetic screening might be used to help reduce the incidence of fractures.…”
Section: Geneticsmentioning
confidence: 99%
“…Unfortunately, these approaches may be cost prohibitive if used on a regular, screening basis and/or they may require general anaesthesia. Alternatively, others have suggested using genetic screening or predictive modelling to identify those horses at greatest risk for catastrophic injuries, 4,[32][33][34] though the utility of these approaches have yet to be proven. While the detection of biomarkers for equine injuries has also been explored, [35][36][37][38][39] their use has not been widely adopted, despite some reported success.…”
Section: Introductionmentioning
confidence: 99%